Amphiphilic polymer-encapsulated Au nanoclusters with enhanced emission and stability for highly selective detection of hypochlorous acid. Issue 24 (20th April 2021) - Li, Yiling; Yi, Shuxiao; Lei, Zhongli; Xiao, Yan
Abstract : Amphiphilic polymer-encapsulated Au nanoclusters with enhanced emission and stability were synthesized and used for the sensitive and selective detection of hypochlorous acid. Abstract : It is of vital importance to develop probes to monitor hypochlorous acid (HClO) in biological systems as HClO is associated with many important physiological and pathological processes. Metal nanoclusters (NCs) are promising luminescent nanomaterials for highly reactive oxygen species (hROS) detection on the basis of their strong reaction ability with hROS. However, metal NCs typically can respond to most common hROS and are susceptible to etching by biothiols, hindering their application in the construction of effective HClO probes. Herein, we proposed a strategy to develop a nanoprobe based on Au NCs for highly sensitive and selective detection of HClO. We synthesized luminescent benzyl mercaptan-stabilized Au NCs and encapsulated them with an amphiphilic polymer (DSPE-PEG). After encapsulation, an obvious emission enhancement and good resistance to the etching by biothiols for Au NCs were achieved. More importantly, the DSPE-PEG encapsulated Au NCs can be used as a nanoprobe for detection of HClO with good performance. The luminescence of the Au NCs was effectively and selectively quenched by HClO. A good linear relationship with the concentration of HClO in the range of 5–35 μM and a limit of detection (LOD) of 1.4 μM were obtained. Additionally, this nanoprobe was successfully used for bioimaging and monitoring of HClO changes in live cells, suggesting the application potential of the as-prepared amphiphilic polymer-encapsulated Au NCs for further HClO-related biomedical research.